2010
DOI: 10.1096/fj.10-163311
|View full text |Cite
|
Sign up to set email alerts
|

Flavokawain B, the hepatotoxic constituent from kava root, induces GSH-sensitive oxidative stress through modulation of IKK/NF-κB and MAPK signaling pathways

Abstract: Kava (Piper methysticum Foster, Piperaceae) organic solvent-extract has been used to treat mild to moderate anxiety, insomnia, and muscle fatigue in Western countries, leading to its emergence as one of the 10 best-selling herbal preparations. However, several reports of severe hepatotoxicity in kava consumers led the U.S. Food and Drug Administration and authorities in Europe to restrict sales of kava-containing products. Herein we demonstrate that flavokawain B (FKB), a chalcone from kava root, is a potent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 57 publications
2
59
1
Order By: Relevance
“…Recent studies have suggested that GSH depletion and post-translational modification of proteins through glutathionylation are related to cell death. GSH is crucial to counteract oxidative stress-induced liver injury as it detoxifies some hepatotoxins and inhibits cell damage induced by hepatotoxins (e.g., Flavokawain B, pyrrolizidine alkaloid, aflatoxin B1 and ethanol) [26][27][28]. In addition to hepatotoxins, GSH is recognized by compounds such as gallic acid, which is widely distributed in plants and foods, and can induce Hela cell death in relation to the ROS and GSH level [29].…”
Section: Signal Transductionmentioning
confidence: 99%
“…Recent studies have suggested that GSH depletion and post-translational modification of proteins through glutathionylation are related to cell death. GSH is crucial to counteract oxidative stress-induced liver injury as it detoxifies some hepatotoxins and inhibits cell damage induced by hepatotoxins (e.g., Flavokawain B, pyrrolizidine alkaloid, aflatoxin B1 and ethanol) [26][27][28]. In addition to hepatotoxins, GSH is recognized by compounds such as gallic acid, which is widely distributed in plants and foods, and can induce Hela cell death in relation to the ROS and GSH level [29].…”
Section: Signal Transductionmentioning
confidence: 99%
“…The principle pharmacological activities of Kava are due to kavalactones, where kavain is the most important. Kavalactones can form electrophilic, quinone metabolites, potentially leading to GSH depletion and oxidative stress (Zhou et al, 2010). Furthermore, kavalactones inhibit CYP-450 enzymes in vitro (Mathews et al, 2002).…”
Section: Kavamentioning
confidence: 99%
“…Recently it was reported that a piperidine alkaloid, pipermethystine (PM), induces apoptosis in human hepatoma HepG2 cells (Nerurkar et al, 2004), but fails to induce hepatic toxicity in vivo (Lim et al, 2007). Furthermore, pipermethystine is not present in significant quantities in roots and rhizomes from the plant used in herbal medicines (Zhou et al, 2010). A new report suggest that the principle damaging substituent is flavokawain B, a lipohophilic chalcone (Zhou et al 2010).…”
Section: Kavamentioning
confidence: 99%
See 1 more Smart Citation
“…This compound was shown to have not only potent antioxidant or free radical-scavenging activities, but also the ability to inhibit cyclooxygenase enzyme cyclooxygenase-1 (COX-1) and COX-2 (7). Yangonin also inhibited LPS-and TNF-α-induced NF-κB activation (8,9); however, the molecular mechanism has not been sufficiently explained. In present study, we investigated the effects of yangonin on the NF-κB activation pathway induced by TNF-α.…”
Section: Introductionmentioning
confidence: 96%